Uncertainty analysis of turbine nozzle guide vane cooling performance - Decang Lou; Mengjun Wang; Along Chen; Jun Zeng; Shuai Zhang; Xiaoyang Huang (PLoS ONE, 2025)
Conjugate heat transfer analysis plays an important role in the design of heavily cooled gas turbine vane or blade. In this study, the aerodynamic and heat transfer performance of the E3 engine nozzle guide vane is investigated through conjugate heat transfer analysis using ANSYS CFX software. Computational fluid dynamic analysis indicates that the shear stress transport turbulence model gives high accuracy in simulating the vane main-stream aerodynamic performance. However, when the simulated surface temperature of the vane was compared with the cooling test data, in which the vane was 3D-printed, significant deviation of the surface temperature distribution was observed. To understand the sources of these deviations, analyses are conducted considering main-stream and coolant flow parameters, as well as manufacturing discrepancies. The results reveal that the large deviation in the manufactured vane (up to 0.5 mm at the leading edge) alters the direction of the coolant flowing out from the leading-edge film-cooling holes, affects the film coverage along the surface, and in consequence, causes the temperature near the stagnation point increasing by approximately 40 K. Furthermore, variations in coolant inlet pressure, decreasing by 10 kPa, and temperature, increasing by 10 K, result in the vane surface temperature increased by 20 ~ 30 K. When the turbulence intensity of the main-stream increased from 5% to 20%, the vane surface temperature increased by approximately 20 K. Hence when conducting conjugate heat transfer analysis to validate the cooling performance of turbine vane or blade, emphasis should be focused on not only the uncertainties of the aerodynamic parameters but the manufacturing deviations.